Trunnionosis: Does Head Size Affect Fretting and Corrosion in Total Hip Arthroplasty? - Del Balso, Christopher; Teeter, Matthew G.; Tan, Sok Chuen; Howard, James L.; Lanting, Brent A. (The Journal of arthroplasty, 2016)
Wear and tribocorrosion at the modular head–neck taper interface may be a cause of failure in metal-on-polyethylene total hip arthroplasty (THA). The present investigation endeavored to elucidate the effect of femoral head diameter on fretting and corrosion in retrieved head–neck tapers. A retrieval analysis of THA prostheses in vivo for a minimum of 1 year was performed. Twenty-three femoral heads of 32-mm diameter were matched with 28-mm heads based on time in vivo and head length (−3 mm to +8 mm). All included implants featured a single taper design from a single manufacturer. Fretting and corrosion damage scoring was performed for each implant under stereomicroscopic visualization. Head diameter was observed to affect fretting (P = .01), with 32-mm femoral heads exhibiting greater total fretting scores than 28-mm heads. Fretting damage was greatest (P = .01) in the central concentric zone of the femoral head bore tapers, regardless of head diameter, length, or stem offset. No significant effect on total corrosion scores was observed for any head or stem variable. Retrieved implant total corrosion scores were positively correlated (ρ = 0.51, P < .001) with implantation time. Increased femoral head diameter in THA may produce greater fretting damage owing to and increased head–neck moment arm. There is no associated increase in corrosion with 28-mm and 32-mm heads of this taper design. The longer a THA prosthesis is implanted, the greater the risk of damage due to corrosion.